2011
DOI: 10.1088/0067-0049/194/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Global X-Ray Properties of the O and B Stars In Carina

Abstract: The key empirical property of the X-ray emission from O stars is a strong correlation between the bolometric and X-ray luminosities. In the framework of the Chandra Carina Complex Project, 129 O and B stars have been detected as X-ray sources; 78 of those, all with spectral type earlier than B3, have enough counts for at least a rough X-ray spectral characterization. This leads to an estimate of the L X -L BOL ratio for an exceptional number of 60 O stars belonging to the same region and triples the number of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
161
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 50 publications
15
161
3
Order By: Relevance
“…However, over recent years, large samples of massive stars with well-established multiplicity properties were studied using XMM-Newton and Chandra (e.g. Sana et al 2006b;Nazé 2009;Nazé et al 2011;Rauw et al 2015a) and revealed that not all massive binaries are indeed X-ray luminous. For instance, O-star binaries with orbital periods of a few days were found to be not particularly bright X-ray sources.…”
Section: Postdoctoral Researcher Frs-fnrs (Belgium) Senior Research mentioning
confidence: 99%
“…However, over recent years, large samples of massive stars with well-established multiplicity properties were studied using XMM-Newton and Chandra (e.g. Sana et al 2006b;Nazé 2009;Nazé et al 2011;Rauw et al 2015a) and revealed that not all massive binaries are indeed X-ray luminous. For instance, O-star binaries with orbital periods of a few days were found to be not particularly bright X-ray sources.…”
Section: Postdoctoral Researcher Frs-fnrs (Belgium) Senior Research mentioning
confidence: 99%
“…Early B stars mark the transition from strong winds / X-ray emitters to weak winds stars / X-ray dark stars toward the rise of coronal X-rays in late A and F type stars. The rate of detection in Xrays among B stars falls to about 50% (Wolk et al 2011;Nazé et al 2011;Berghoefer et al 1997). Little is known about windwind collision in binaries with B-type non-supergiant companions.…”
Section: Introductionmentioning
confidence: 98%
“…They are very bright, L X ∼ 10 31 -10 33 erg s −1 , but this X-ray emission only represents ∼ 10 −7 of their bolometric luminosity (Nazé et al 2011).…”
Section: X-ray Emission Processes For Ob Starsmentioning
confidence: 98%